Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1175/1520-0442(2002)015<1389:lbsrvo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between Summer Rainfall Variability over South America and Sea Surface Temperature Anomalies

Abstract: A reconstructed rainfall dataset, and satellite estimates are used to analyze interannual to decadal variability of austral summer precipitation over South America. Rotated empirical orthogonal function (REOF) analysis is applied to isolate dominant patterns of rainfall. Links of these patterns to sea surface temperature anomalies (SSTAs) are examined. The leading mode is related to El Niño-Southern Oscillation (ENSO), which explains 12% of the total variance. During warm ENSO events, the positive phase of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 51 publications
6
101
0
4
Order By: Relevance
“…Moreover, during Pacific warm events, the enhanced subtropical jet acts like a barrier, inhibiting frontal systems to go northward over the continent, and confining them to the south. Paegle and Mo (2002) suggested that the ENSOrelated PSA wave train increases the pressure gradient between the Chaco low and the Atlantic subtropical high, contributing to an increased supply of moisture and enhanced precipitation over eastern Brazil.…”
Section: The Remote Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, during Pacific warm events, the enhanced subtropical jet acts like a barrier, inhibiting frontal systems to go northward over the continent, and confining them to the south. Paegle and Mo (2002) suggested that the ENSOrelated PSA wave train increases the pressure gradient between the Chaco low and the Atlantic subtropical high, contributing to an increased supply of moisture and enhanced precipitation over eastern Brazil.…”
Section: The Remote Responsementioning
confidence: 99%
“…Kalnay et al, 1986;Garreaud and Battisti, 1999;Mo, 2000;Cavalcanti, 2000;Paegle and Mo, 2002). In general, the anomalous warm water associated with ENSO events induces changes in the Hadley and Walker circulations, generating Rossby wave trains that affect the South American rainfall (Grimm, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because the South Atlantic plays a key role in the energy transport towards the North Atlantic and influences the climate over South America, a better understanding of the basin-scale SST variability is required. Several studies (Paegle and Mo, 2002, and references therein) have diagnosed strong links between rainfall variability over South America and SST conditions in the South Atlantic. Recently, Robertson et al (2002) examined the atmospheric response to oceanic anomalies in the tropics and subtropics of the South Atlantic based on AGCM simulations and found strong, statistically significant signals on the atmospheric lowlevel circulation and precipitation on interannual time scales.…”
Section: Introductionmentioning
confidence: 98%
“…During ENSO warm phase convection intensifies over western tropical South America with consequent suppression over eastern tropical South America (e.g. Zhou and Lau 2001;Paegle and Mo 2002). Grimm et al (2007) showed that during the austral spring El Niño events induce subsidence over the Amazon and eastern Brazil, decreasing moisture convergence and precipitation in these regions.…”
Section: Introductionmentioning
confidence: 99%